Asuhan Akupunktur pada Pasien Gastroesophageal Reflux Disease (GERD) Disertai Kecemasan Sosial Studi Kasus di Makassar Holistic Care - Zulkifli Busri; Puspo Puspo; Ikwan Ikwan (Journal of Innovative and Creativity (Joecy), 2026)
Gastroesophageal Reflux Disease (GERD) is a gastrointestinal disorder that can be accompanied by psychological symptoms, including social anxiety. The relationship between psychological and gastrointestinal factors can be understood through the bidirectional communication of the brain-gut axis. In Traditional Chinese Medicine (TCM), a patient's condition is assessed via syndrome differentiation, which serves as the basis for determining therapeutic principles and acupuncture points. This study describes acupuncture care for a GERD patient with social anxiety based on TCM syndrome differentiation at Makassar Holistic Care. A longitudinal descriptive case study was conducted on a 26-year-old male patient who received 12 acupuncture sessions over six weeks, at a frequency of twice weekly. The points utilized included LR3 (Taichong), ST36 (Zusanli), PC6 (Neiguan), CV12 (Zhongwan), GB34 (Yanglingquan), and SP6 (Sanyinjiao). Evaluation was performed using the Gastroesophageal Reflux Disease Questionnaire (GERDQ), medical history taking, the Four Diagnostic Methods (Si Zhen), and clinical observation. The GERDQ score decreased from 13 to 5 after 12 sessions, accompanied by a reduction in heartburn, regurgitation, sleep disturbances, social anxiety, and the use of symptomatic medication. Acupuncture care based on TCM syndrome differentiation demonstrated positive clinical progress. However, the results of a single-case study lacking a control group and standardized psychometric measurements cannot prove a causal link regarding acupuncture's effectiveness, nor can the findings be generalized..